2015
DOI: 10.1074/jbc.m115.663526
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-related Apoptosis-inducing Ligand (TRAIL)-Troglitazone-induced Apoptosis in Prostate Cancer Cells Involve AMP-activated Protein Kinase

Abstract: Background: Combination of TRAIL with PPAR␥ ligands has been shown to ameliorate TRAIL resistance, but the mechanism involved is still unknown. Results: Inhibition of AMPK activity antagonizes TRAIL and troglitazone combination-induced apoptosis and attenuates caspase cleavage in prostate cancer cells. Conclusion: AMPK is involved in mediating TRAIL-troglitazone-induced apoptosis. Significance: Targeting AMPK by TRAIL and troglitazone combination might be an effective means of sensitizing apoptosisresistant pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 51 publications
0
18
1
Order By: Relevance
“…The effect of PPAR-γ ligands on cell growth inhibition and apoptosis has been investigated in various cancers 47 . Recent research has showed that knockdown of PPAR-γ expression reduces the cleavage of caspase 3 during the early stages of apoptosis 48 . Moreover, studies have documented that PPAR-γ activation might be a promising target for osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of PPAR-γ ligands on cell growth inhibition and apoptosis has been investigated in various cancers 47 . Recent research has showed that knockdown of PPAR-γ expression reduces the cleavage of caspase 3 during the early stages of apoptosis 48 . Moreover, studies have documented that PPAR-γ activation might be a promising target for osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the AMPK‐activators may work well in combination with chemotherapy, indicating that AMPK activity is associated with antitumor efficacy. Recently, biguanides, the first line pharmacotherapy for glucose control, appeared to activate AMPK and improve response to chemotherapy by removing cancer stem cell in a variety of cancers: Also, thiazolidinediones (TZDs), a class of insulin‐sensitizing drugs, activate AMPK both directly and indirectly via the induction of adiponectin, leading to tumor suppression . Due to these findings, according to http://clinicaltrials.gov (https://clinicaltrials.gov/ct2/home), there are currently many trials of biguanides or TZDs for cancer mainly in combination with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, biguanides, the first line pharmacotherapy for glucose control, appeared to activate AMPK 7 and improve response to chemotherapy by removing cancer stem cell in a variety of cancers 39,40 : Also, thiazolidinediones (TZDs), a class of insulin-sensitizing drugs, activate AMPK both directly and indirectly via the induction of adiponectin, leading to tumor suppression. 41,42 Due to these findings, according to ClinicalTrials.gov (https://clinicaltrials.gov/ct2/ home), there are currently many trials of biguanides or TZDs for cancer mainly in combination with chemotherapy. As for predicting the effect of these drugs, AMPK pathway-related SNPs may be promising markers.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway is stimulated during late-stage prostate cancer and may represent an essential survival mechanism [16][17][18][19]. Activated AMPK induces autophagy, promotes mitochondrial biogenesis and is involved in apoptosis [18,20,21], thereby fostering prostate cancer growth and survival, whereas silencing AMPK expression reduces prostate cancer cell proliferation and migration [13,22]. However, other studies report that AMPK has a tumor suppressor role in prostate cancer [19,[23][24][25], so that potent and selective chemical probes [26] will be essential to understand the enigmatic function of AMPK in cancer and other pathologies [2,3,9,12].…”
Section: Introductionmentioning
confidence: 99%